Internet finance in China : introduction and practical approaches - Xie, Ping; Zou, Chuanwei; Liu, Haier (London : Routledge, 2020)
Internet finance deals specifically with the impacts of internet-based technologies, such as mobile payments, social networks, search engines, cloud computation, and big data, on the financial sector. This book, as a detailed report on internet finance in China, will help readers understand the status quo and development of China's financial system.
usc 04/11/2022
Keywords: Internet banking; Mobile commerce; Big data; China